Schiller : national poet - poet of nations ; a Birmingham symposium - Martin, Nicholas (Amsterdamer Beiträge zur neueren Germanistik ;, 2006)
To mark the 200th anniversary of Schiller's death, leading scholars from Germany, Canada, the UK and the USA have contributed to this volume of commemorative essays. These were first presented at a symposium held at the University of Birmingham in June 2005. The essays collected here shed important new light on Schiller's standing as a national and transnational figure , both in his own lifetime and in the two hundred years since his death. Issues explored include: aspects of Schiller's life and work which contributed to the creation of heroic and nationalist myths of the poet during the nineteenth and early twentieth centuries; his activities as man of the theatre and publisher in his own, pre-national context; the (trans-)national dimensions of Schiller's poetic and dramatic achievement in their contemporary context and with reference to later appropriations of national(ist) elements in his work. The contributions to this volume illuminate Schiller's achievements as poet, playwright, thinker and historian, and bring acute insights to bear on both the history of his impact in a variety of contexts and his enduring importance as a point of cultural reference.